P172 Preclinical evidences of the therapeutic potential of ABTL0812 in endometrial cancer. (1st November 2019) - Gil-Moreno, A; Felip, I; Moiola, CP; Megino-Luque, C; Lopez-Gil, C; Cabrera, S; Solé-Sánchez, S; Muñoz-Guardiola, P; Megias-Roda, E; Pérez-Montoyo, H; Alfon, J; Yeste-Velasco, MY-V; et al.
Abstract : Introduction/Background: Endometrial cancer (EC) is the most frequent of the infiltrating tumors of female genital tract. Surgical and adjuvant treatments are the cornerstone treatment for EC patients, however, the response rate to standard therapy is very limited, highlighting the need for novel and efficient treatments. ABTL0812, a small first-in-class molecule, induces cancer cell death by inhibiting the PI3K/AKT/mTOR pathway (frequently overactivated in EC) and inducing endoplasmic reticulum stress (ER-Stress). Objective: Assess the preclinical efficacy of ABTL0812 in EC. Methodology: We studied ABTL0812 treatment on viability, autophagy and apoptosis in a wide panel of EC cell lines and in 3D-murine endometrial organoids. ABTL0812 efficacy was evaluated in tumor onset and progression in a tamoxifen-inducible PTEN-KO murine model and cell line- or patient-derived xenograft (PDX) models. TRIB3 mRNA levels were evaluated in blood from EC patients recruited in ongoing Phase 1b/2a clinical trial. Results: We demonstrated that ABTL0812 treatment in vitro reduced viability, sensitized cancer cells and induced autophagy through ER-stress induction and PI3K/AKT/mTORC1 axis inhibition. In murine PTEN-KO cells, ABTL0812 decreased proliferation and induced nuclear fragmentation/condensation and caspase activation. ABTL0812 in vivo therapeutic benefit was confirmed, leading to a marked reduction in tumor growth (p<0.05), impairing the initial progression of endometrial tumorigenesis in PTEN-KO mouse model, and inhibiting tumor progression in PDX models, potentiating carboplatin-paclitaxel treatment. Finally, ABTL0812 increased TRIB3 mRNA levels after 8h of treatment in blood of human patients. Conclusion: Our results demonstrated that ABTL0812 treatment promoted autophagy followed by activation of the pro-apoptotic pathway. Collectively, we provided strong preclinical evidences of the therapeutic benefit of ABTL0812 as monotherapy or in combination with current first-line treatment in EC. Our findings present a novel and clinically applicable therapeutic strategy for EC and suggest the potential use of TRIB3 as a pharmacodynamic biomarker to monitor ABTL0812 treatment. Disclosure: Sonia Solé-Sánchez, Pau Muñoz-Guardiola, Elisabet Megias-Roda, Héctor Pérez-Montoyo, José Alfon, Marc Yeste-Velasco, Carles Domènech are Ability Pharmaceuticals employees. Carles Domènech CD holds shares of the Company. José Miguel Lizcano is member of its Scientific Advisory Board. Antonio Gil-Moreno, Isidre Felip, Cristian Pablo Moiola, Cristina Megino-Luque, Carlos Lopez-Gil, Silvia Cabrera, María Santacana, Xavier Dolcet, Armando Reques, Ana Oaknin, Victor Rodríguez-Freixinos Xavier Matias-Guiu, Eva Colas, Nuria Eritja, declare no conflicts of interest.